Stemming The Tide Of Hypertension In Women: Optimal Age For Obstetric Debut - Basil N Okeahialam (Journal of Preventive Medicine And Care, 2023)
Objective Women have continued to bear a heavy burden of cardiovascular disease morbidity and mortality with hypertension as the flagship. This is partly because as the modifiable cardiovascular disease risk factors are falling in rate, gender specific risk factors have persisted. One of them is age at first pregnancy and delivery. Methods In order to contribute to this discourse, we secondarily analysed data generated in a previous field study on risk factors for cardiovascular diseases in free living adults in Plateau State, Nigeria. The women were divided into four groups and we looked at blood pressure at the time of study from the perspective of age at first pregnancy. Reults It was found that those who had their first pregnancy in the late teenage years had the lowest mean arterial blood pressure many years down the line; better than those who started child bearing earlier and those who started later. There was also significant within and between group differences in the blood pressures (p = 0.000). Conclusion To stem the tide of female hypertension later in life, child bearing should not start in the early teenage years nor be unnecessarily delayed. Sociocultural conditions that promote early teenage marriage and pregnancy should be discouraged.
Keywords: Hypertension